O estatuto dos itens lexicais [que] e [o que] contidos nas relativas - Nickel, Rejane (2017)
This work aimed to define the statute of the lexical items [que] and [o que] in relatives of the Brazilian Portuguese, through the scope of the studies in generative syntax. The research happened because there is divergence in generative literature to these lexical items. Concerning to the lexical item [que], while some authors consider it only a complementizer (inspired in Chomsky, 1977and Kayne, 1994 who had analyzed [that]) other authors consider it a relative pronoun which introduces head relatives (KATO, 1993; KATO; NUNES, 2009). Referring to the lexical item [o que] there is divergence, too. One of the analysis is that [o que] is the bond between a demonstrative and a complementizer (CAPONIGRO, 2003). The second, which is the most acceptable for the generative authors, is that the item is a relative pronoun (MÓIA, 1992; FERREIRA, 2007; MARCHESAN, 2012). Through the divergence of the statute of these items in the Brazilian Portuguese, this dissertation aimed to answer the following questions: a) Which is the statute of the lexical items [que] and [o que] in the relatives?; b) Can [que] and [o que] introduce any kind of relatives?; c)What are the properties of the relative pronouns and complementizers?; d) What are the contributions that the studies of Brazilian Portuguese can give to the distinction of these lexical items?; and e) Considering the available derivations in the literature, which seems to be the most suitable to the relatives? The results of this research showed that [que] and [o que] are relative pronouns. [que] introduces head relatives, that, according Kato (1993) has being lost lexical function, because it can be substituted by [o qual], also, other relative pronouns are losing their lexical function but still are relative pronouns and through diachronic data and other relative pronouns are allowed in resumptives, not only [que]. [O que] is a relative pronoun similar to [what] from English, which introduces free relatives and head relatives with preposition, because it doesn‟t allowed to be substituted by demonstratives in infinitive sentences and, in other languages (like Catalan) [o] can‟t be head of a relative. Besides, in this research, it was considered the LD model (KATO (1993); KATO; NUNES (2009)) the most suitable to the head relatives because it can explain the relativization strategies on Brazilian Portuguese and it considers [que] a relative pronoun and Comp Hypothesis (GROOS; VAN RIEMSDIJK (1981)) to the free relatives because it comprises the biggest number of relative types (appositive and restrictive) and it respect the island conditions.